2013
DOI: 10.1111/cei.12144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term sitagliptin treatment on immune parameters in healthy individuals, a randomized placebo-controlled study

Abstract: SummarySitagliptin, a dipeptidyl-peptidase 4 (DPP-4) inhibitor, improves blood glucose control in patients with type 2 diabetes by blocking cleavage of glucagon-like peptide 1 (GLP-1). In type 2 diabetes patients sitagliptin use is associated with an increase in minor infections, and in new-onset type 1 diabetes patients the ability of sitagliptin to dampen autoimmunity is currently being tested. DPP-4, also known as CD26, is expressed on leucocytes and can inactivate many chemokines important for leucocyte mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Effective and during the study consistent inhibition of the blood plasma DPP-IV enzymatic activity upon regular sitagliptin administration was achieved and was similar to the results of other authors [19]. This observation indirectly argues for treatment compliance in the majority of the patients during our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Effective and during the study consistent inhibition of the blood plasma DPP-IV enzymatic activity upon regular sitagliptin administration was achieved and was similar to the results of other authors [19]. This observation indirectly argues for treatment compliance in the majority of the patients during our study.…”
Section: Discussionsupporting
confidence: 91%
“…In the study by Aso et al however, no elevation of Th1 cells was observed and the authors reported a decrease of lymphocyte and CD4 + cell counts [20]. None of these changes were seen in a study evaluating healthy subjects without prior history of diabetes or impairment of glucoregulation treated with sitagliptin for four weeks [19].…”
Section: Discussionmentioning
confidence: 91%
“…Whereas the majority of successful antipsoriatic medications are immunosuppressive, none of the hypoglycemic agents show evidence of suppression of the immune system [78][79][80][81] . These medications are frequently used in the diabetic population without complication, and the side effects are well tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier consultation from endocrinology may be beneficial. Hypoglycemic agents are commonly used, safe, well tolerated, and are unlikely to be immunosuppressive [78][79][80][81] . For patients in which immunosuppression is contraindicated, off-label usage of hypoglycemic agents may be warranted to control severe psoriasis and improve quality of life while avoiding the toxic effects of other systemic therapies.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies demonstrate that the use of sitagliptin in individuals with T1D improved overall the glycemic control and reduced insulin requirements without altering the amount of endogenous insulin production (8). Although great controversy exists in available data (8, 9), it has been proven that DPP-4 (also known as adenosine deaminase complexing protein 2 or CD26) is a transmembrane glycoprotein encoded by the DPP4 gene. CD26 is expressed by many cell types including lymphocytes and is associated with immune regulation.…”
Section: Discussionmentioning
confidence: 99%